RUSSIA-TURKEY RELATIONS AND NON-GOVERNMENTAL ACTORS (NGOS) - (:unkn) unknown (ISTANBUL UNIV, 2016)
Turkey-Russia relations are generally considered and studied as state to state relations. However, together with the increasing volume of trade and human mobility, it could be claimed that Non-Governmental Actor's also started to have a role in this relationship. Businessman associations, social groups that exist out of mixed marriages, various ethnic groups, Russian Orthodox Church, religious authorities that represent Russian Muslims and scientists are the actors that are focused within the scope of this article. The methods they use, potentials and limits of their influence are tried to be analyzed in this article.
Keywords: Turkish Foreign Policy; Russia's Turkey Policies; NGOs; Businessmen Associations; Mixed Marriages; Ethnic Groups; Orthodox Church